PD-1 blockage combined with vaccine therapy can facilitate immune infiltration in tumor microenvironment of Lynch syndrome colon cancer - Ye, Kai; Zhong, Wenjin; Wang, Pengcheng; Chen, Yanxin; Chi, Pan (Frontiers in Genetics, 2022)
Background: Lynch syndrome is a genetic disease resulting from mismatch repair gene mutation. Vaccine therapy can enhance the immunogenicity of Lynch syndrome and improve the therapeutic efficacy of immunotherapy. However, there is no approved Lynch syndrome vaccine coming onto the market. Methods: Herein, we used gene knockdown method to construct Lynch syndrome cell model, paving way for us to develop Lynch syndrome tumor lysate vaccine. Then the isograft technique was employed for constructing the tumor-bearing mouse model of Lynch syndrome. And this isograft model was treated with PD-1 monoclonal antibody and tumor vaccine, respectively. Flow cytometry was used for detecting the proportion of immune cells and immunosuppressive cells, and ELISA was used for detecting the contents of chemokines and cytokines in the blood circulation system and tumor tissues of mice. Finally, IHC was used to detect the effects of tumor vaccines as well as PD-1 antibody on tumor tissue proliferation and angiogenesis. Results: The results demonstrated that tumor vaccine could prolong the overall survival of mice, and improve the disease-free survival rate of mice. The vaccine could increase the proportion of inflammatory cells and decrease the proportion of anti-inflammatory cells in the blood circulation system of mice. In addition, tumor vaccine could also improve inflammatory infiltration in the tumor microenvironment and reduce the proportion of immunosuppressive cells. The results of IHC showed that tumor vaccine could inhibit angiogenesis and tumor cell proliferation in mouse tumor tissues. Conclusion: In colon cancer associated with Lynch syndrome, tumor vaccine can hinder the growth of tumor cells, and assist immunotherapy whose therapeutic effect on this kind of cancer is thus enhanced.